Patrimonio cultural y turismo comunitario en la parroquia Pungalá, cantón Riobamba, provincia de Chimborazo - Piaún Chalcualán, Diego Paul (2024)
ABSTRACT: The objective of this research project is to analyze the relationship between cultural heritage and community tourism in Pungalá Parish, Riobamba City, Chimborazo Province. Addressing the problematic situation that is the waste of cultural heritage that leads to deficient tourism development. The research methods used are documentary, field, descriptive, and quantitative. The research design is non-experimental and correlational. In addition, the application of the survey technique was considered, using the Likert scale questionnaire as an instrument that is aimed to the inhabitants of the Pungalá Parish (Cultural Heritage) and to the representatives of the parish GAD (Community Tourism) to collect data about the study variables and their dimensions. Subsequently, with the use of the SPSS Statistics program, a hypothesis test was carried out using Pearson's R where it was proven that there is no relationship between cultural heritage and community tourism. Finally, based on the results obtained, a cultural revitalization plan was proposed to strengthen community tourism in the Pungalá Parish to take advantage of and value the tourist attractions and cultural festivities for greater development of tourism.